2023
DOI: 10.3390/ijms24129826
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Axis and Vestibular Physiopathology: From Animal Model to Pathology

Abstract: A recent work of our group has shown the significant effects of thyroxine treatment on the restoration of postural balance function in a rodent model of acute peripheral vestibulopathy. Based on these findings, we attempt to shed light in this review on the interaction between the hypothalamic–pituitary–thyroid axis and the vestibular system in normal and pathological situations. Pubmed database and relevant websites were searched from inception through to 4 February 2023. All studies relevant to each subsecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…A total of 131 articles were initially identified. After excluding duplicates, thyroid autoimmune diseases, and articles unrelated to the subject, 20 articles were retained [2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], providing access to the full text. The stages in the data collection process are described in Figure 1.…”
Section: Collection Of Bibliographical Datamentioning
confidence: 99%
“…A total of 131 articles were initially identified. After excluding duplicates, thyroid autoimmune diseases, and articles unrelated to the subject, 20 articles were retained [2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], providing access to the full text. The stages in the data collection process are described in Figure 1.…”
Section: Collection Of Bibliographical Datamentioning
confidence: 99%
“…A study by Serra et al found altered glucose and insulin levels in patients with peripheral vestibular disorders [103]. Congenital hypothyroidism, among other organs, also has a negative effect on inner ear development [104]. A connection between the inner ear and thyroid cells has also been found concerning exposure to gravity, which modulated the thyroid cells in a study by Grimm [105].…”
Section: The Vestibular System-associated Networkmentioning
confidence: 99%